Analysing the efficiency of the Johannesburg Stock Exchange using the magic formula - Vincent, Christopher John (My University, 2018)
This study examined the efficiency of South African markets, namely the Johannesburg Stock Exchange (JSE) through the use of a value investing strategy called the “magic formula”, which was created by Joel Greenblatt and published in his 2006 book “the little book that beats the market”. This study back tested the magic formula on the JSE from 2000 to 2016. It ranked stocks according to the magic formula methodology, using earnings yield and return on capital to derive portfolios. The portfolios were then compared against the JSE All Share Index (the market). The magic formula showed evidence of outperformance of the market over the period, even when accounting for risk. The magic formula was compared against other portfolios derived from value investing ratios, namely ROA, ROE and EY. The ROA portfolio produced the best risk-adjusted results, but all value investing portfolios outperformed the market providing evidence against efficient markets.
A thesis submitted to the Faculty of Commerce, Law and Management, Wits Business School at the University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Management in the field of Finance & Investment, February 2018
Keywords: Johannesburg Stock Exchange; Efficient market theory